Religion and Popular Music jrfm - Natalie Fritz (Journal for Religion, Film and Media, 2020)
The interactions between popular music and religion are manyfold and highly complex. Popular music as an important part of popular culture is a means of communication. Music can transmit not only emotions and a sense of community but also religious knowledge, knowledge that leaves diverse traces in different times and places. In the end, whether we extract religious meaning from popular music and what that meaning is depend on our background and on our capacity to contextualise symbols, motives and narratives - and also on the media used to convey these references. By analysing Florence + The Machines song "Big God" and its music video we will address some of the questions that arise while working in the field of popular music and religion.